2013
DOI: 10.1002/tox.21866
|View full text |Cite
|
Sign up to set email alerts
|

Phoxim-induced damages ofBombyx morilarval midgut and titanium dioxide nanoparticles protective role under phoxim-induced toxicity

Abstract: Phoxim (O,O-diethyl O-(alpha-cyanobenzylideneamino) phosphorothioate) is a powerful organophosphorus pesticide with high potential for Bombyx mori larvae of silkworm exposure. However, it is possible that during the phoxim metabolism, there is generation of reactive oxygen species (ROS) and phoxim may produce oxidative stress and neurotoxicity in an intoxicated silkworm. Titanium dioxide nanoparticles (TiO2 NPs) pretreatment has been demonstrated to increase antioxidant capacity and acetylcholinesterase (AChE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…Moreover, it has also been shown that AgNPs with organic additive 1 exhibited cytotoxicity of mammalian cells, HepG2 cells as compared to AgNPs with organic additive 3 which exhibited lower cell toxicity of HepG2 cells (34). It is noteworthy to mention that TiO 2 NPs enhanced the antioxidant system against phoxim-induced oxidative stress in Bombyx mori (25). Further, it has been suggested that TiO 2 NPs have ability to act at the level of expression of resistancerelated genes and their proteins, including those encoding SOD, CAT, GPX, and GST, which in turn mitigate ROS in B. mori larvae under BmNPV infection (35).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, it has also been shown that AgNPs with organic additive 1 exhibited cytotoxicity of mammalian cells, HepG2 cells as compared to AgNPs with organic additive 3 which exhibited lower cell toxicity of HepG2 cells (34). It is noteworthy to mention that TiO 2 NPs enhanced the antioxidant system against phoxim-induced oxidative stress in Bombyx mori (25). Further, it has been suggested that TiO 2 NPs have ability to act at the level of expression of resistancerelated genes and their proteins, including those encoding SOD, CAT, GPX, and GST, which in turn mitigate ROS in B. mori larvae under BmNPV infection (35).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we demonstrated that citrate-coated AgNPs plays an important role in energy metabolism as evidenced by a balance between aerobic to anaerobic marker enzymes succinate dehydrogenase and lactate dehydrogenase, respectively in AH infected fishes (8). Further, titanium dioxide nanoparticles protect silkworm, Bombyx mori against phoxim induced oxidative stress and neurotoxicity (24,25). Thus, it seems obvious that response of biological systems towards different combinations of NPs differ at the perspective of toxicological aspects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pre-treatment by TiO 2 NPs increased antioxidant capacity and acetylcholinesterase (AChE) activity in intoxicated silkworm and improved B. mori larval survival under phoxim-induced toxicity [199]. TiO 2 NPs pre-treatment also reduced the phoxim-induced brain damage of the 5th larval instar of B. mori; under phoxim exposure they relieved severe brain damage and oxidative stress in the brain and inhibited the down-regulated expression of H + -transporting ATP synthase and vacuolar ATP synthase that are involved in ion transport and energy metabolism [200].…”
Section: Nanoinsecticidesmentioning
confidence: 99%